Endoscopic full-thickness resection of superficial colorectal neoplasms using a new over-the-scope clip system: A single-centre study. Issue 9 (September 2017) - Andrisani, Gianluca; Pizzicannella, Margherita; Martino, Margareth; Rea, Roberta; Pandolfi, Monica; Taffon, Chiara; Caricato, Marco; Coppola, Roberto; Crescenzi, Anna; Costamagna, Guido; Di Matteo, Francesco Maria
Abstract: Background and aim: Endoscopic full-thickness resection (EFTR) provides complete en-bloc resection with a histopathological evaluation of submucosal, muscular, and serosal layers. The aim of this study was to investigate the efficacy and safety of a novel over-the-scope device for colorectal EFTR. Material and methods: In this retrospective, observational, open-label case study, a total of 20 patients with superficial colorectal neoplasms, underwent EFTR using a new endoscopic full-thickness resection device (FTRD; Ovesco Endoscopy, Tübingen, Germany). Endoscopic treatment outcomes (technical success, rate of EFTR, adverse events) and early follow-up at three months, were analyzed. Results: We reported a 100% of technical success, defined as full-thickness resection. Among the R1 resections, histology was negative for neoplasm. Non-lifting adenomas had histology positive for adenocarcinoma: seven T1/G1/sm1; one T1/G1/sm2; one, who underwent a surgical resection, T1/G1/sm3. Mean size of the resected lesions was 26 mm, ranging from 10 to 42 mm. One (5%) patient developed abdominal pain, fever and leukocytosis and was treated conservatively with medical therapy. In all specimens, histological complete resection was confirmed. Conclusions: EFTR is a feasible and effective technique that could become a valid alternative to EMR and ESD in the management of recurrent adenomas, no-lifting lesions and scars of R1 resections. However, prospective studies are needed to further evaluate the device and technique.